2019
DOI: 10.1111/jfbc.12948
|View full text |Cite
|
Sign up to set email alerts
|

Enzymolysis of walnut ( Juglans regia L.) meal protein: Ultrasonication‐assisted alkaline pretreatment impact on kinetics and thermodynamics

Abstract: To improve the utility of walnut meal protein, influences of ultrasonication on the kinetic and thermodynamic constraints of enzyme (trypsin) hydrolysis were assessed using a multi‐frequency counter current S‐type ultrasound machine. Results revealed that both the ultrasonication treatment and control hydrolysis obeyed the first‐order kinetics within the study constraints. After 90 min hydrolysis time, the uppermost percentage conversion rate (57.5%) of substrate to product and the percentage increase (25.42%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…Therefore, the acceleration of protein extraction was connected with the changes of protein microstructure induced by ultrasound. And this effect was also observed in ultrasound-assisted treatment systems involving walnut protein [42] . Microstructure influenced the chemical and physical properties, and functionality of the protein.…”
Section: Resultsmentioning
confidence: 60%
“…Therefore, the acceleration of protein extraction was connected with the changes of protein microstructure induced by ultrasound. And this effect was also observed in ultrasound-assisted treatment systems involving walnut protein [42] . Microstructure influenced the chemical and physical properties, and functionality of the protein.…”
Section: Resultsmentioning
confidence: 60%
“…Jambrak et al [33] reported same trend of foaming properties for ultrasonically treated soy protein and wheat gluten [34] . The increase in surface hydrophobicity values may also be responsible for improving the foaming capacity and stability which might be due to the exposure of hydrophobic groups to accelerated adsorption at the gas/water interface [35] .…”
Section: Resultsmentioning
confidence: 99%
“…The mechanical and shear force produced during ultrasound cavitation opens up the protein structure resulting in the molecular unfolding via peptide bond disruption (Ren, Zhang, Liang, Hou, & Zhou, 2017). These increased surface area coupled with tissue porosity, loosening/sponginess and unfolded protein structure could prove beneficial in further processing and subsequent increase in the bioactivity of the WMPs via peptide production (Golly et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The multi‐frequency countercurrent S‐type ultrasound apparatus (MFSU) (WKS 300/6S) employed in this study was developed by our research group in Jiangsu University and produced by Jiangsu Jiangda Wukesong Biotechnology Co., Ltd., China. This equipment has been fully described in our previous work (Golly et al, 2019). The device is equipped with five distinct frequencies; 20, 28, 35, 40, and 52 kHz and powered from five ultrasonic generators.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation